Methods for Delineating Degraded Land at Citarum Watershed, West Java, Indonesia - Tarigan, Suria Darma (UNIVERSITY OF LAMPUNG, 2012)
Accurate information on the extent and spatial location of degraded lands is very important to plan their rehabilitation. So far, various institutions issue different estimation on the extent of degraded land in Indonesia led to big confusion for rehabilitation planning.Â Ministry of Forestry estimates around 30.2 million ha of degraded land both inside and outside forestry area throughout Indonesia based on data released in 2007. Ministry of Forestry implementes the so called scoring method in delineating degraded land. Criteria used in the scoring methods are: land cover, slope steepness, erosion, and management. Scoring method applies different weight to each of those criteria. This study aimed to analyze accuracy of scoring method and to compare it to propose alternative methods in delineating degraded land such as: a) Inconsistency of land use, and b) Combination of Inconsistency of land use and scoring method. The accuracy of these methods were obtained by comparing to the field observation. The slope map was derived from SRTM 30 m, soil map was obtained from Soil Research Institute and land cover/land use from Ministry for Environment.Â Using GIS analysis, those maps were used to compose land capability classification (LCC) and inconsistency of land use. The study showed that scoring method had 66% accuracy in delineating degraded land. When scoring method was combined with Inconsistency method the accuracy increased about 7%.Keywords: Degraded land; inconsistency of land use; land capability class; scoring method[How to Cite: Tarigan SD. 2012. Methods for Delineating Degraded Land at Citarum Watershed, West Java, Indonesia. J Trop Soils, 17 (3): 267-274. doi: 10.5400/jts.2012.17.3.267][Permalink/DOI: www.dx.doi.org/10.5400/jts.2012.17.3.267]